Review on Software Ecosystem: An Emerging Area (International Journal of Engineering and Computer Science, 2014)
A software product line (SPL) companies expanding their platform outside their organization, which is now termed as a software ecosystem approach. This approach investigates the relationship between companies in software industry. Companies work together with co-ordination to achieve their strategic goals. In this paper we undertake a review on the software ecosystem as an emerging area. This paper also described challenges, implications and new approach of software ecosystem as business perspective rather than only technical. We have focused on three dimensional perspectives of software ecosystem as technical, social and business including most recent investigated areas of software ecosystem. This paper emphasis on the, research areas needed to develop sustainable software ecosystem